Carbon ion radiotherapy of hepatocellular carcinoma provides excellent local control: the prospective phase I PROMETHEUS trial - Hoegen-Saßmannshausen, Philipp; Naumann, Patrick; Hoffmeister-Wittmann, Paula; Harrabi, Semi B.; Seidensaal, Katharina; Weykamp, Fabian; Mielke, Thomas; Ellerbrock, Malte; Habermehl, Daniel; Springfeld, Christoph; Dill, Michael T.; Longerich, Thomas; et al. (JHEP reports, 2024)
Background & Aims - Inoperable hepatocellular carcinoma (HCC) can be treated by stereotactic body radiotherapy. However, carbon ion radiotherapy (CIRT) is more effective for sparing non-tumorous liver. High linear energy transfer could promote therapy efficacy. Japanese and Chinese studies on hypofractionated CIRT have yielded excellent results. Because of different radiobiological models and the different etiological spectrum of HCC, applicability of these results to European cohorts and centers remains questionable. The aim of this prospective study was to assess safety and efficacy and to determine the optimal dose of CIRT with active raster scanning based on the local effect model (LEM) I. - Methods - CIRT was performed every other day in four fractions with relative biological effectiveness (RBE)-weighted fraction doses of 8.1-10.5 Gy (total doses 32.4-42.0 Gy [RBE]). Dose escalation was performed in five dose levels with at least three patients each. The primary endpoint was acute toxicity after 4 weeks. - Results - Twenty patients received CIRT (median age 74.7 years, n = 16 with liver cirrhosis, Child-Pugh scores [CP] A5 [n = 10], A6 [n = 4], B8 [n = 1], and B9 [n = 1]). Median follow up was 23 months. No dose-limiting toxicities and no toxicities exceeding grade II occurred, except one grade III gamma-glutamyltransferase elevation 12 months after CIRT, synchronous to out-of-field hepatic progression. During 12 months after CIRT, no CP elevation occurred. The highest dose level could be applied safely. No local recurrence developed during follow up. The objective response rate was 80%. Median overall survival was 30.8 months (1/2/3 years: 75%/64%/22%). Median progression-free survival was 20.9 months (1/2/3 years: 59%/43%/43%). Intrahepatic progression outside of the CIRT target volume was the most frequent pattern of progression. - Conclusions - CIRT of HCC yields excellent local control without dose-limiting toxicity. - Impact and implications - To date, safety and efficacy of carbon ion radiotherapy for hepatocellular carcinoma have only been evaluated prospectively in Japanese and Chinese studies. The optimal dose and fractionation when using the local effect model for radiotherapy planning are unknown. The results are of particular interest for European and American particle therapy centers, but also of relevance for all specialists involved in the treatment and care of patients with hepatocellular carcinoma, as we present the first prospective data on carbon ion radiotherapy in hepatocellular carcinoma outside of Asia. The excellent local control should encourage further use of carbon ion radiotherapy for hepatocellular carcinoma and design of randomized controlled trials. - Clinical Trials Registration - The study is registered at ClinicalTrials.gov (NCT01167374).
Enthält Graphical abstract
Gesehen am 28.01.2025